A 3-day high-fat/low-carbohydrate diet does not alter exercise-induced growth hormone response in healthy males. Issue 6 (December 2015) - Sasaki, Hiroto; Ishibashi, Aya; Tsuchiya, Yoshihumi; Shimura, Nobuhiro; Kurihara, Toshiyuki; Ebi, Kumiko; Goto, Kazushige
Abstract: Objective: The purpose of the present study was to examine the effects of 3 days isoenergetic high-fat/low-carbohydrate diet (HF-LC) relative to low-fat/high-carbohydrate diet (LF-HC) on the exercise-induced growth hormone (GH) response in healthy male subjects. Design: Ten healthy young males participated in this study. Each subject consumed the HF-LC (18 ± 1% protein, 61 ± 2% fat, 21 ± 1% carbohydrate, 2720 kcal per day) for 3 consecutive days after consuming the LF-HC (18 ± 1% protein, 20 ± 1% fat, 62 ± 1% carbohydrate, 2755 kcal per day) for 3 consecutive days. After each dietary intervention period, the hormonal and metabolic responses to an acute exercise (30 min of continuous pedaling at 60% of V ˙ O2max ) were compared. The intramyocellular lipid (IMCL) contents in the vastus lateralis, soleus, and tibialis anterior were evaluated by proton magnetic resonance spectroscopy. Results: Serum GH concentrations increased significantly during the exercise after both the HF-LC and LF-HC periods ( P  < 0.05). However, the exercise-induced GH response was not significantly different between the two periods. Fat utilization and lipolytic responses during the exercise were enhanced significantly after the HF-LC period compared with the LF-HC period. IMCL content did not differ significantly in any portion of muscle after the dietary interventions. Conclusions: We could not show that short-term HF-LC consumption changed significantly exercise-induced GH response or IMCL content in healthy young males. Highlights: It could not be confirmed that a 3-day high-fat/low-carbohydrate diet altered significantly exercise-induced growth hormone response despite of increased FFA level. Exercise-induced lipolytic and fat-oxidative responses were enhanced by consumption of high-fat/low-carbohydrate diet for three days. Intramyocellular lipid contents did not change after short-term consuming high-fat/low-carbohydrate diet.